Measuring the benefits of ICTs in social enterprises: an exploratory study - Marcelo Okano; Celi Langhi; Rosinei Batista Ribeiro (BBR: Brazilian Business Review)
The study presented in this article aims to identify what are, in fact, the social missions of companies called “social companies” , and what are the benefits obtained from the use of ICTs by these companies. The research methods employed were bibliographic research and case study. The bibliographic research was elaborated from a systematic analysis and the use of a theoretical framework related to performance indicators, as proposed by Hutchinson and Molla (2009). The case study was carried out based on four social companies, with which observations were made in loco, application of interviews and analysis of the respective websites. The results indicated that the social mission of this type of company can be explained by the use of six indicators: access to markets, income generation, employment opportunities, social training, strengthening of relations with the sponsor and social outsourcing; and that these indicators require the use of ICTs to be developed. It is concluded that, if at least one of the indicators is present in these companies, ICTs can bring some kind of benefit.